DEVELOPMENT OF CANVA-ASSISTED POWERPOINT LEARNING MEDIA FOR TEACHING ADDITIVE SUBSTANCES TO EIGHTH-GRADE STUDENTS - Alim, Samiul; Arinna Manasikana, Oktaffi Arinna (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2026)
The use of a blackboard as a learning medium and an explanation of the subject matter delivered orally so far often occurs at Mbah Bolong Islamic Junior High School in Diwek Jombang, especially in additive material which results in students feeling bored and difficult to understand the material so that an innovative and varied learning media is needed so that students are always interested in learning at school, one of which is learning additives and making it easier for students to understand additive material. Canva-assisted power point learning media is offered as an innovative and varied solution to make learning additives more interesting and fun. The purpose of this study was to develop a power point learning media assisted by Canva which was tested for validity in class VIII additives. This type of research uses research and development (R&D) with the ADDIE model which consists of four stages, namely: Analyze, Design, Development, and Evaluation. The results of the validation of the canva-assisted power point learning media that have been developed are included in the very valid category with an average percentage obtained from validators (Media Experts, Material Experts, and Teacher Practitioners) which is 91%.